Classification and evaluation of episiotomy practices from 2004 to 2020 and association with OASIS. Issue 1 (4th February 2022) - Morgan, Rosemary; Korb, Diane; Sibony, Olivier
Abstract: Objective: To apply a new classification based on seven clinically relevant subgroups to accurately describe episiotomy practices and evaluate the association between episiotomy and obstetrical anal sphincter injury (OASIS) rates according to the classification's subgroups. Methods: Observational retrospective cohort study based on a population comprising 39 487 women from January 1, 2004 to December 31, 2020 in a level III university maternity unit. The primary outcome was the overall episiotomy rate in the institution and its trend over time as well as in each subgroup of obstetrical population classification. Secondary outcome was the rate of third‐ and fourth‐degree OASIS, and its association with episiotomy practice. Results: The episiotomy rate decreased significantly from 43.2% to 20% in the total population. The overall OASIS rate was 0.34%; it remained significantly the same during the study period, although the association between OASIS and episiotomy was significant only in group 2 (nulliparous women with instrumental delivery) with a decrease of OASIS rate if using episiotomy (odds ratio 0.5; 95% confidence interval 0.3–0.8). Conclusion: The episiotomy rate can be decreased without exposing women to an increased risk of OASIS. This encourages restrictive practice of episiotomy, but episiotomy should be considered in nulliparous women with instrumental delivery. Abstract : The contents of this page will be used as part of issue TOC only. It will not be published as part of main article. Association between OASIS and episiotomy was significant only among nulliparous women with instrumental delivery, with a decrease of OASIS rate if using episiotomy.